Lengthening Temporalis Myoplasty: Virtual Animation-Assisted Technical Video. Issue 3 (September 2016) - Aljudaibi, Nawaf; Bennis, Yasmine; Duquennoy-Martinot, Veronique; Labbé, Daniel; Guerreschi, Pierre
Abstract : Summary: Lengthening temporalis myoplasty is a well-established procedure for dynamic palliative reanimation of the lip in facial palsy sequelae. The particularity of this technique is that the entire temporal muscle is transferred from the coronoid process to the upper half of the lip without interposition of aponeurotic tissue. To date, no video describing the technique was available. This is the first video describing the entire procedure, from preoperative markings through postoperative rehabilitation. In the video presented herein, the authors craft virtual three-dimensional animations in addition to a live operation on a patient performed by Daniel Labbé, who first described this technique 20 years ago. Abstract : Video Plus Content is available in the Text.